Workplace Diversity and the Performance of Coca-Cola Company in Benin City, Edo State, Nigeria - Abraham Ejogba Orhero; Ugo Chuks Okolie (Universitas Medan Area, 2023)
In this study, the performance of the Coca-Cola Company in Benin City, Edo State, Nigeria was evaluated in relation to workplace diversity. A survey research design was used, along with a method of systematic random sampling. For this study, a questionnaire was used as the research tool for data collection, and 148 respondents were deemed useful. The study's theoretical framework was based on social identity theory. Statistical Package for Social Sciences (SPSS) software version 23.0 was used to perform a linear regression analysis and a Spearman's rank correlation coefficient on the collected data. The study's findings demonstrated that workplace diversity significantly improved the performance of Coca-Cola Company, Benin City, Nigeria. According to expectations, the study also showed a positive and significant correlation between workplace diversity and the performance of the Coca-Cola Company, Benin City, Nigeria. The study comes to the conclusion that it is critical for employers and policymakers to comprehend shifting workforce demographics and the effects of growing diversity on employee behavior. Tensions over cultural issues are likely to increase as the workforce becomes more diverse. As a result, the study suggests, among other things, that organizational leaders/managers enforce cultural mentoring, which is one of the tried-and-true ways to help managers and employees, both new and old, adjust to their roles and the workplace.